Periodontal disease and FAM20A mutations - Piranit Nik Kantaputra (2018)
© 2017 The Japan Society of Human Genetics All rights reserved. Enamel-renal-gingival syndrome (ERGS; OMIM #204690), a rare autosomal recessive disorder caused by mutations in FAM20A, is characterized by nephrocalcinosis, nephrolithiasis, amelogenesis imperfecta, hypoplastic type, gingival fibromatosis and other dental abnormalities, including hypodontia and unerupted teeth with large dental follicles. We report three patients and their families with findings suggestive of ERGS. Mutation analysis of FAM20A was performed in all patients and their family members. Patients with homozygous frameshift and compound heterozygous mutations in FAM20A had typical clinical findings along with periodontitis. The other had a novel homozygous missense mutation in exon 10, mild gingival fibromatosis and renal calcifications. The periodontitis in our patients may be a syndrome component, and similar findings in previous reports suggest more than coincidence. Fam20a is an allosteric activator that increases Fam20c kinase activity. It is hypothesized that lack of FAM20A activation of FAM20C in our patients with FAM20A mutations might have caused amelogenesis imperfecta, abnormal bone remodeling and periodontitis. Nephrocalcinosis appears not to be a consistent finding of the syndrome and the missense mutation may correlate with mild gingival fibromatosis. Here we report three patients with homozygous or compound heterozygous mutations in FAM20A and findings that extend the phenotypic spectrum of this disorder, showing that protein truncation is associated with greater clinical severity.